The Effect of Frailty on Outcome After Vascular Surgery. (November 2019) - Visser, Linda; Banning, Louise B.D.; El Moumni, Mostafa; Zeebregts, Clark J.; Pol, Robert A.
Abstract : Objectives: Frailty is a state of increased vulnerability and is a stronger predictor for post-operative outcome than age alone. The aim of this study was to determine whether frailty is associated with adverse 30 day outcome in vascular surgery patients. Methods: This was a prospective cohort study. All electively operated vascular surgery patients between March 2010 and October 2017 ( n = 1201), aged ≥ 60 years were evaluated prospectively. Exclusion criteria were arteriovenous access surgery, percutaneous interventions and minor amputations, resulting in 825 patients for further analysis whereas 195 had incomplete data on Groningen Frailty Indicator (GFI) and were excluded. Frailty was measured using the GFI, a screening tool covering 16 items in the domains of functioning. Patients with a total score of ≥4 were classified as frail. The primary outcome parameter was 30 day morbidity (based on the Comprehensive Complication Index). Secondary outcome measures were 30 day mortality, hospital readmission, and type of care facility after discharge. Outcomes were adjusted for sex, body mass index, smoking status, hypertension, Charlson Comorbidity Index, and type of intervention. Results: There was an unequal sex distribution (77.6% male). The mean age was 72.1 years. One hundred and eighty-four patients (22.3%) were considered frail. The mean Comprehensive Complication Index was 8.5. Frail patients had a significantly higher Comprehensive Complication Index (3.7 point increase, p = .005). Patients with impaired cognition and reduced psychosocial condition, two domains of the GFI, had a significantly higher Comprehensive Complication Index. Also, the 30 day mortality rate was higher in frail patients (2.7 point increase; p = .05), and they were discharged to a care facility more often (7.7 point increase; p < .001). There was no significant difference in readmission rates between frail and non-frail patients. Conclusions: Frailty is associated with a higher risk of post-operative complications and discharge to a nursing home after vascular surgery. Some frailty domains (mobility, nutrition, cognition and psychosocial condition) appear to have a more pronounced impact.